Education for sustainable development: Melestari kecerdasan interpersonal dan intrapersonal anak-anak yatim Perlis - Azid @ Aziz, Nurulwahida; Yaacob, Aizan; Saidin, Khaliza (Universiti Utara Malaysia, 2014)
The development of minority children should be given utmost attention particularly in their education.Orphans have always been associated with low confidence, self-esteem and having poor communication skills. These children’s potential should be enhanced so that they could build their self- esteem and positive mindsets to overcome challenges in their lives.Studies have shown that children from minority group have low interpersonal and intrapersonal intelligences. Thus, it is felt that more attention on these two aspects should be examined.The objectives of this study were to identify the participants’ interpersonal and intrapersonal intelligence profiles based on gender and types of orphanage, and to examine the impact of treatment activities on their intelligence profiles.2 orphanages and 46 children were involved in the treatment group using “One-group pre-test and post-test design”. This study adopted both quantitative and qualitative methods.The findings revealed that the treatment activities have increased the participants’ intrapersonal and interpersonal intelligences.T-test reported significant difference between the pre-test and post- test of their interpersonal intelligence (t=-16.730, df = 45, p<.05), and there was also significant difference in t heir intrapersonal intelligence ((t=-13.160, df = 45, p<.05).The interview findings also indicated that the respondents were positive about themselves after the treatment. Our findings indicated that even though this small scale study cannot be generalized, the treatment could be applied to any minority groups in other contexts.